Avicenna`s Point about Bladder Gas as a Cause of Interstitial Cystitis - Malihe TABARRAI; Zahra NIKTABE; Nematollah MASOUDI; Tahereh EFTEKHAAR (Tehran University of Medical Sciences, 2018)
Avicenna`s Point about Bladder Gas as a Cause of Interstitial Cystitis